Relative Effectiveness of Classroom Interaction Techniques on Senior Secondary Students’ Silence and Confusion in Government Classrooms in Port Harcourt Metropolis - Onwioduokit, F.A.; Chika, Oranu Philomena (Richtmann Publishing, 2012)
This study sought to identify the relative effectiveness of classroom interaction techniques on senior secondarystudents’ silence and confusion in Government classroom in Port Harcourt Local Government, Rivers State, Nigeria. Tworesearch questions guided the study; two hypotheses were tested and analyzed using chi square statistics. The population ismade up of 580 students and six teachers. Students in SS1 and SS11 in three public schools constituted the sample. Fourclassrooms were used; two SS1 classes and two SS11 classes respectively. Three teachers taught SS1 classes and threeteachers taught SS11 classes using a techniques( Flanders, IRE, and Teaching Cycles). Twelve lessons were recorded on acassette, transcribed and coded. Flanders category was the observational instrument. Test- retest method was used to establishthe reliability of the instrument at 0.87 co- efficient. The result showed that students’ silence and confusion is not contingent onclass level. Silence and confusion are part of the continuum in every classroom. Re-conceptualizing silence and confusion in theclassrooms could go a long way in enhancing student participation and engagement.